Testing Integration and Cointegration: An Overview. - Banerjee, A; Hendry, D (1992)
The paper exposits Wiener distribution theory for I(1) time series as an overview to a special issue on testing integration and cointegration. The behavior of an I(1) series is related to a Wiener process to derive the limiting distribution of its sample mean. Other Wiener processes are related to functions of the normal distribution. The analysis is applied to an autoregressive process, a bivariate regression, and the similarity and power properties of two single-equation tests for cointegration. Systems analyses of cointegration based on the Johansen approach are derived by successive concentration of the likelihood function. An empirical model for Norwegian consumption expenditure is examined.